2018
DOI: 10.37358/rc.18.2.6130
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Morphologic Analysis of Titanium Dental Implants: X-ray Photoemission Techniques (XPS) and Scanning Electron Microscopy (SEM) with EDX Analysis

Abstract: Nowadays the implants rehabilitations are used deeply by clinicians. The importance to technological improvement is working to find the best surface of the fixture to obtain a good and stable osteointegration. By the use of the Energy Dispersive X-ray (EDX) analysis and the X-ray Photoemission Spectroscopy (XPS) evaluate the surface quality of commercial implants. The XPS analysis was made to evaluate the chemical elements that compose the material surface of the implant and determine the state of atomical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Aluminum oxide and corundum (the naturally occurring mineral form of Al 2 O 3 ) are deposited during the sandblasting process and seem to have differential effects according to their concentrations. In fact, it was pointed out that high concentrations of residual Al reduce mineralization and osseointegration, while lower concentrations [43,44] have positive effects on cell viability [36] and may be advantageous for bone formation and mineralization [45] and stem cell differentiation [44]. Fluorine surface treatment has been found to clearly affect actin filaments and cell morphology [38,46] and influence cell differentiation, but not proliferation [38,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum oxide and corundum (the naturally occurring mineral form of Al 2 O 3 ) are deposited during the sandblasting process and seem to have differential effects according to their concentrations. In fact, it was pointed out that high concentrations of residual Al reduce mineralization and osseointegration, while lower concentrations [43,44] have positive effects on cell viability [36] and may be advantageous for bone formation and mineralization [45] and stem cell differentiation [44]. Fluorine surface treatment has been found to clearly affect actin filaments and cell morphology [38,46] and influence cell differentiation, but not proliferation [38,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Saline [28] Sodium hypochlorite [26] Sodium hydroxide [33] Improve osteoconduction and osteointegration [33] Enhance early stage of cell adhesion, proliferation, and differentiation [34] Cause precipitation of many minerals, higher wear resistance of the implant surface [28,[33][34][35] Aluminium Sand-blasting [37] Acid etching [37] Physiological fluids [15] Ti-Al coating [38] Enhance corrosion resistant [15] Improved osteoblast viability [22] Interfere osseointegration process [39] [15,22,[37][38][39]…”
Section: Sodiummentioning
confidence: 99%
“…Some Ti dental implants may contain surface contaminants that may cause a problem during the osseointegration process. A study done by Semez et al [38] showed that the amount of Al in a dental implant called MYIM-PLANT (Nobel Biocare, India) was 12-fold higher than that found in Ti alloys typically used for dental implants (between 0 and about 0.06) [38]. Furthermore, another study suggested that a high concentration of residual aluminium oxide (AlO 2 ) may interfere negatively with the osseointegration process [39].…”
Section: Aluminium (Al)mentioning
confidence: 99%
“…The surface chemistry and properties are key factors of the implant’s long life since the surface of the implant is in direct contact with surrounding bones of the oral cavity [ 1 ]. Therefore, many commercially available implants made of metals, alloys, and ceramics have been intensively explored to evaluate their surface properties [ 2 , 3 , 4 ]. The results revealed the presence of inorganic and organic contaminants on many implants.…”
Section: Introductionmentioning
confidence: 99%